Improving Numeracy Performance Through a Digitized 5-Minute Drill - Mary Grace Campomayor (Indonesian Journal of Mathematics Education, 2026)
The continuous decline in numeracy performance among Filipino learners highlights the need for technology-supported instructional strategies. This study examined the effectiveness of a digitized 5-minute drill in improving learner’s numeracy skills in a public elementary school. Twenty-two learners (14 male, 8 female) participated in a quasi-experimental study using a reflexive comparison design. Pretest and posttest assessments aligned with the Mathematics curriculum were administered to measure changes in performance. Results revealed a statistically significant improvement in learners’ scores, with the mean increasing from 14.50 in the pretest to 16.09 in the posttest (p = .03 ). The findings suggest that short, consistent, and technology-assisted drills can effectively enhance learners’ mastery of the four fundamental operations. The study highlights the potential of digital timed practice as an accessible and scalable strategy for strengthening foundational numeracy skills in mathematics education. Further research may investigate other digital formats and examine their effects on higher-order mathematical competencies.